Strengthening MSME Financial Reporting Quality: The Role of Internal Control Systems and Human Resource Competencies - Syla Arifatus Sholiha; Arwan Gunawan (FEBI IAIN Langsa, 2026)
This study demonstrates that internal control systems and human resource competence have a positive and significant impact—both individually and simultaneously—on the quality of financial reports for MSMEs in Rawalumbu District, Bekasi City. The internal control system emerges as the dominant factor in enhancing the quality of financial reporting by strengthening the control environment, control activities, transaction documentation, and effective oversight mechanisms. Human resource competence also contributes to the production of financial reports that are relevant, reliable, comparable, and understandable in accordance with SAK EMKM standards. These findings were derived using instruments based on the COSO (2013) framework for internal control systems, SAK EMKM (IAI, 2016) for financial report quality, and Spencer and Spencer (1993) for human resource competence, with data analyzed via multiple linear regression. This research addresses a gap in the literature by providing limited empirical evidence that simultaneously examines the synergy between internal control systems and human resource competence in local government-supported MSMEs as they implement SAK EMKM. The study’s novelty lies in integrating these two variables as internal organizational capabilities—viewed through the lens of the Resource-Based View (RBV)—within the context of MSMEs supported by the Bekasi City Cooperatives and SMEs Agency; this yields a model demonstrating that financial report quality is influenced not only by each factor in isolation but also by the synergy between them. These findings enrich the literature on MSME financial governance and offer practical implications for local governments and support agencies to develop accounting training programs, strengthen internal control systems, and provide sustained guidance on SAK EMKM implementation, thereby enhancing MSME accountability and competitiveness.